DAMPAK PROGRAM E-WARUNG TERHADAP KESEJAHTERAAN MASYARAKAT KOTA PEKANBARU TAHUN 2017 - Ali, Rahmat Eka Saputra; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Ministry of Social Affairs (Kemensos) launched the Warung Warung (e-Warung) program which is based on the Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 25 of 2016 concerning the assistance of developing business funds through Electronics Warung mutual cooperation business groups together with family hope programs. The establishment of the e-Warung program aims to improve the welfare of the beneficiary families of social assistance in the hope of reducing poverty in Indonesia. e-Warung is a new program launched by the government to provide subsidies to disadvantaged communities so that their lives can be more prosperous. The e-Warung program was inaugurated in January 2017. The purpose of this study was to find out how the e-Warung program affected the welfare of the people of Pekanbaru in 2017. This study used descriptive quantitative research methods. This research was conducted at the Office of Social Affairs and Cemetery of Pekanbaru City and e-Warung in the city of Pekanbaru. Data collection techniques are done by distributing questionnaires to respondents and documentation to support analysis and interpretation of data. While data analysis was carried out using statistical techniques with SPSS 16.0 for windows programs and using descriptive statistics to complete the data analysis used in the study. Based on the testing of the determinant coefficient, the R value of 0.780 was found which means that the e-Warung program on people's welfare has a strong influence with a value of 78%. And the value of the coefficient of determination (Rsquare) of 0.609 means that the variation in the change in the dependent variable (Community Welfare) is able to be explained by the change in the independent variable (e-Warung Program) by 60.9%. This research proves that the e-Warung program has a strong impact on the welfare of the people of Pekanbaru. Keywords : e-Warung, Welfare, Community